Evaluation of Sayang Beta Website Using UTAUT Method in Adolescents and Adults - Mufidaturrizqiyah Mufidaturrizqiyah; Sylvia Caradine Resalda; Nuril Dipa Fatahillah; Haikal Haikal; Hanif Pandu Suhito; Prahita Indriana Raniasmi; Sholikun Sholikun (Dian Nuswantoro Semarang, 2026)
The Sayang Beta website is a digital health information media developed by the Semarang City Health Office to improve adolescent and early adult health literacy. This study aims to evaluate user acceptance of the Sayang Beta Website using the Unified Theory of Acceptance and Use of Technology (UTAUT) method. The study used a quantitative approach with a cross-sectional design of 108 respondents, who were selected through accidental sampling techniques. Data were collected using a Likert scale questionnaire and analyzed using multiple linear regression. The results of the study show that the UTAUT model is able to explain the intention to use the Sayang Beta Website well. The Adjusted R Square value of 0.695 shows that 69.5% of behavioral intention is influenced by the variables of performance expectancy, effort expectancy, social influence, and facilitating conditions. Partially, performance expectancy (sig = 0.008), social influence (sig = 0.012), and facilitating conditions (sig = 0.010) had a significant effect on behavioral intention, while effort expectancy had no significant effect (sig = 0.269). This study concludes that the Sayang Beta Website has potential as a digital health literacy media, but it needs further development in terms of language, usage guidelines, visual content variations, and promotional strategies so that its use is more optimal